Monoclonal antibody therapy of herpes simplex virus: An opportunity to decrease congenital and perinatal infections - Backes, Iara M.; Leib, David A.; Ackerman, Margaret E. (Frontiers in Immunology, 2022)
The fetal/neonatal period represents both a unique window of opportunity for interventions as well as vulnerability to a number of viral infections. While Herpesviruses such as herpes simplex virus (HSV) are highly prevalent and typically of little consequence among healthy adults, they are among the most consequential infections of early life. Despite treatment with antiviral drugs, neonatal HSV (nHSV) infections can still result in significant mortality and lifelong neurological morbidity. Fortunately, newborns in our pathogen-rich world inherit some of the protection provided by the maternal immune system in the form of transferred antibodies. Maternal seropositivity, resulting in placental transfer of antibodies capable of neutralizing virus and eliciting the diverse effector functions of the innate immune system are associated with dramatically decreased risk of nHSV. Given this clear epidemiological evidence of reduced risk of infection and its sequelae, we present what is known about the ability of monoclonal antibody therapies to treat or prevent HSV infection and explore how effective antibody-based interventions in conjunction with antiviral therapy might reduce early life mortality and long-term morbidity.